Kinetic study of the transformation of sodalite to nepheline. Issue 6 (29th January 2022) - Padilla, Isabel; López‐Delgado, Aurora; Romero, Maximina
Abstract: The kinetics and mechanism of the development of nepheline (NaAlSiO4 ) through thermal transformation of sodalite (Na4 Al3 Si3 O12 Cl) was studied by means of differential thermal analysis at different heating rates (10°C min −1 to 50°C min −1 ) to control the evolution of the crystallization fraction. The conversion of sodalite (cubic crystal) to pure nepheline (hexagonal crystal) took place in the 800°C–900°C interval. The activation energy for nepheline crystallization from sodalite was determined by isothermal and non‐isothermal methods. The ratio t 0.75 / t 0.25, together with the Avrami exponent ( n ) and the numerical factor of the dimensionality of crystal growth ( m ) parameters indicated that dominant crystallization mechanism in nepheline development is bulk crystallization mechanism controlled by interface reaction.